2001
DOI: 10.1016/s0304-3940(01)01926-7
|View full text |Cite
|
Sign up to set email alerts
|

High-voltage-activated Ca2+ currents and the excitability of pyramidal neurons in the hippocampal CA3 subfield in rats depend on corticosterone and time of day

Abstract: High-voltage-activated Ca2+ currents and the excitability of pyramidal neurons in the hippocampal CA3 subfield in rats depend on corticosterone and time of day Kole, MHP; Koolhaas, JM; Luiten, PGM; Fuchs, E Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. AbstractThis study tested the time-of-day dependence of the intrinsic postsynaptic properties of hippocampal CA3 pyramidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…It is noteworthy that in the absence of corticosteroid hormones (or with reduced levels of GRs), sustained calcium current amplitude was also high (Karst et al, 1994;Hesen et al, 1996), revealing a U-shaped dose dependence (Joëls, 2006). A similar U-shaped dose dependence was also described for CA3 neurons, when correlating circulating corticosteroid levels throughout the day with the calcium current amplitude (Kole et al, 2001). By contrast, dentate granule cells do not show an enhanced calcium current amplitude several hours after they have Rapid effects of corticosteroid hormones on cognitive processing in male rodents.…”
Section: A Slow Modulation Of Neural Activitysupporting
confidence: 54%
See 2 more Smart Citations
“…It is noteworthy that in the absence of corticosteroid hormones (or with reduced levels of GRs), sustained calcium current amplitude was also high (Karst et al, 1994;Hesen et al, 1996), revealing a U-shaped dose dependence (Joëls, 2006). A similar U-shaped dose dependence was also described for CA3 neurons, when correlating circulating corticosteroid levels throughout the day with the calcium current amplitude (Kole et al, 2001). By contrast, dentate granule cells do not show an enhanced calcium current amplitude several hours after they have Rapid effects of corticosteroid hormones on cognitive processing in male rodents.…”
Section: A Slow Modulation Of Neural Activitysupporting
confidence: 54%
“…8); this differs from the situation of predominant MR activation (such as occurs under rest), which is characterized by more spikes during a depolarizing pulse than in the absence of steroids (Joëls and de Kloet, 1990), reflecting the same U-shaped dose dependence as observed with respect to calcium current amplitude. Similar effects were also seen in the CA3 area (Kole et al, 2001). The onset of the corticosterone-dependent modulation in firing frequency is slow and requires protein synthesis (Karst and Joëls, 1991).…”
Section: Mr + Gr Mr Adxsupporting
confidence: 53%
See 1 more Smart Citation
“…1 B, C). As glutamate transmission is persistently enhanced by corticosteroids, calcium would continue to enter hippocampal cells [5,136,137] . This would cause NMDA receptors in the hippocampus to desensitize in order to protect the cells from excitotoxicity [138][139][140][141][142] .…”
Section: Effects Of Stress On Hippocampal Synaptic Plasticitymentioning
confidence: 99%
“…Researchers have documented diurnal and circadian differences in long-term potentiation in the hippocampus (10,11). Additional studies have also found that excitability of CA3 neurons is regulated diurnally (12). Thus, some mechanisms exist for learning and memory to be rhythmic.…”
mentioning
confidence: 99%